FACTORS INFLUENCING ORGANIZATIONAL BEHAVIOR AT THE OFFICE OF THE MINISTRY OF RELIGION OF PASAMAN REGENCY - Dian, Dian; Salnida, Salnida; Sumiati, Sumiati (Komunitas Manajemen Kompetitif, 2025)
This study aims to see the influence of (1) Religiosity on the OCB of employees of the Pasaman Regency Ministry of Religion Office. (2) Transformational leadership style on the OCB of employees of the Pasaman Regency Ministry of Religion Office. (3)Physicological capitaltowards the OCB of employees of the Ministry of Religion Office of Pasaman Regency. (4) Work environment towards the OCB of employees of the Ministry of Religion Office of Pasaman Regency. (5) Job satisfaction towards the OCB of employees of the Ministry of Religion Office of Pasaman Regency. (6) Religiosity, transformational leadership style, psychological capital, work environment and job satisfaction together affect the OCB of employees at the Pasaman Regency Ministry of Religion Office. The population in this study was allemployees of the Ministry of Religious Affairs Office of Pasaman Regency as many as 44 people. The sampling technique in this study used the total sampling technique or population sample. Where the sample in this study was all employees of the Ministry of Religious Affairs Office of Pasaman Regency as many as 32 people. The results of this study show that(1) Religiosity has a significant effect on the OCB of employees at the Pasaman Regency Ministry of Religion Office. (2) Transformational leadership style has a significant effect on the OCB of employees at the Pasaman Regency Ministry of Religion Office. (3) Psychological capital has a significant effect on the OCB of employees at the Pasaman Regency Ministry of Religion Office. (4) The work environment has a significant effect on the OCB of employees at the Pasaman Regency Ministry of Religion Office. (5) Job satisfaction has a significant effect on the OCB of employees at the Pasaman Regency Ministry of Religion Office. (6) Religiosity, transformational leadership style, psychological capital, work environment and job satisfaction together have a significant effect on the OCB of employees at the Pasaman Regency Ministry of Religion Office..